Parents‘ and healthcare professionals’ perception toward the introduction of a new fully liquid hexavalent vaccine in the Malaysian national immunization program: a cross-sectional study instrument development and its application - Al Bashir, Lama; Ismail, Aniza; Aljunid, Syed Mohamed (Frontiers in Immunology, 2023)
A newly developed fully liquid hexavalent vaccine that comprises six antigens for Diphtheria, Tetanus, acellular Pertussis, Inactivated Poliomyelitis, Haemophilus Influenza type b., and Hepatitis B, is proposed to be introduced in the Malaysian national immunization program, instead of the non-fully liquid pentavalent vaccine and monovalent Hepatitis B vaccine that is currently employed in the immunization schedule. Although the introduction of new vaccines is a necessary intervention, it still needs to be accepted by parents and healthcare professionals. Hence, this study aimed to develop three structured questionnaires and to investigate the participants’ perception and acceptability toward the incorporation of the new fully liquid hexavalent vaccine. A cross-sectional study was conducted among a sample of 346 parents, 100 nurses, and 50 physicians attending twenty-two primary health care centers in the states of Selangor and the Federal Territory of Kuala Lumpur and Putrajaya during 2019-2020. The study found that Cronbach’s alpha coefficients for the study instruments ranged from 0.825 to 0.918. Principal components analysis produced a good fit with KMO>0.6. For the parents’ perception questionnaire, the only extracted factor explained 73.9 % of the total variance; for the nurses’ perception toward a non-fully and fully liquid combined vaccine, there was a sole extracted factor that explained 65.2 % and 79.2% of the total variance, respectively. Whereas for the physicians’ perception, there was one factor extracted that explains 71.8 % of the total variance. The median score for all the questionnaire items ranged from 4 to 5 (Q1 and Q3 vary between 3-5). Parents' ethnicity was significantly associated (P-value ≤ 0.05) with the perception that the new hexavalent vaccine would reduce their transportation expenses. Moreover, a significant association (P-value ≤ 0.05) was found between physicians' age and the perception of the hexavalent vaccine's ability to decrease patient overcrowding in primary healthcare centers. The instruments used in this study were valid and reliable. Parents of Malay ethnicity were the most concerned about transportation expenses since they have the lowest income and are more concentrated in rural areas compared to other races. Younger physicians were concerned about reducing patient crowding and hence reducing their workload and burnout.